2021
DOI: 10.35877/454ri.qems309
|View full text |Cite
|
Sign up to set email alerts
|

Women and Small Business: Contributing to Household income and Family wellbeing

Abstract: The objective of the study is to examine the extent to which women involvement is small business contributes to household income and family wellbeing. The study adopted the survey research method in collecting data from 317 women from Yala Local Government Area of Cross River State, Nigeria using Cluster and Purposive sampling technique. The Survey Monkey Sample Determinant Technique was used to determine the sample size for the study. The instrument of data collection was a semi-structured self-developed ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…In addition, educational attainment of women and employment position were found to be the most important determinants of their empowerment and participation in decision-making in all aspects of their household life. A study by Iji et al [13] indicated that 97.41% of women in their research did not rely primarily on their partners' earnings. 63.70% of women used all of the money they earned to care for their houses.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, educational attainment of women and employment position were found to be the most important determinants of their empowerment and participation in decision-making in all aspects of their household life. A study by Iji et al [13] indicated that 97.41% of women in their research did not rely primarily on their partners' earnings. 63.70% of women used all of the money they earned to care for their houses.…”
Section: Introductionmentioning
confidence: 94%
“…Dalam tulisannya ia melihat adanya asosiasi positif antara status pernikahan, terutama di kalangan perempuan dengan self-employement atau memperkerjakan diri sendiri, dalam hal ini adalah entrepreneurship atau kewirausahaan (Molina, 2020). Sementara (Iji et al, 2021) pada studi mereka, dalam konteks masyarakat Nigeria memperlihatkan bahwa perempuan dalam usaha kecil mereka berkontribusi pada pendapatan rumah tangga dan kesejahteraan keluarga (Iji, Ebong, & Ojong-Ejoh, 2021). Berdasarkan konsep-konsep tersebut peneliti akan menjawab rumusan masalah pertama, yaitu peran ibu wirausaha dalam memenuhi kebutuhan keluarga terutama pada masa pandemi COVID-19.…”
Section: Kerangka Teoritisunclassified